The Challenges and Orientation of Islamic Education at the Border Location: Case Study of MTs Al-Ikhlas Nunukan - Eko Nani Fitriono (CV. Creative Tugu Pena, 2023)
Educational issues were essential in efforts to improve the quality of human resources. It’s based on the mandate in the preamble of the 1945 Constitution. That’s why equal distibution of education in all areas was a right for citizens, including at the border of Indonesia, especially the Nunukan area, North Kalimantan. The article was to reveal information or data related to the challenges and orientation of Islamic education in Nunukan Regency. The method used field research in the form of qualitative-descriptive method. The location of this research was at MTs Al-Ikhlas Nunukan. The subjects of this study were students, educators, and Madrasah administrators at MTs Al-Ikhlas Nunukan. The results showed that to overcome various madrasah problems, formulations were needed, namely: integrating Islamic values ​​in science and social learning, maximizing religious practices, applying good exemplary and habituation models, as well as reward and punishment related to student morals. Keywords: Challenge and Orientation Education, Islamic Education, Education at Border Location